Lima Barreto e redes de sociabilidades : uma leitura a partir dos seus internamentos psiquiátricos, práticas epistolares e obra (1908-1922) - Silva, Roseilda Maria da (Universidade do Vale do Rio dos Sinos, 2022)
This thesis aims to investigate the psychiatric admittances of Afonso Henriques de Lima Barreto, based on political, social, personal, educational and family experiences (1908-1922). We analyze the writer’s sociability network formation and epistolary practices in order to understand how the interaction with his correspondents took place, what the missives showed on Lima Barreto the writer, and how his health and admittances appear in his writing, especially in the novel O Cemitério dos Vivos (The Cemetery of the Living), and on the notes from Diário do Hospício (Diary of the Asylum). From Rio de Janeiro, a black intellectual, chronicler, literary critic, editor and founder of the Floreal magazine, collaborator for others, author of a vast literary work, son of a typographer and a teacher, this was Lima Barreto. He lived in a context of significant transformations and felt the impacts of the First Republic, period in which class relationship, race, degeneration, whitening, hygiene, criminality, alcoholism and madness were in evidence. The methodological perspective adopted in this study is based on microhistory discussions. We have established a dialogue with History of Emotions, Intellectual History and History of Epistolary Practices, essential perspectives to perceive and narrate Lima Barreto’s experiences, in the relation with society’s more general themes in that period. The sources analyzed were biographies about the writer, letters written and received by him, within the time frame of the study, the novel O Cemitério dos Vivos and Diário do Hospício, besides other writing that comprise his work set, as well as authors that analyzed the First Republic, the Psychiatric Hospital and Madness. The study shows that in his childhood, Lima Barreto was faced with hardships, however, he had access to an education that was destined to the elite, which interfered in his intellectual development. He maintained contact with a large sociability network, which indicates his acknowledgement as a writer; even though he was faced with opposition when he presented his literary project. Lima Barreto was admitted in a psychiatric hospital twice, turning his experience into literary reflection, in which he rebutted criticism on attributing alcoholism to heredity. The admittances did not interrupt his literary practice, as he was still questioning and conscientious. However, his later health weakening made socialization difficult. He remained secluded in his home until his last days.
Keywords: Lima Barreto; Práticas epistolares; Redes de sociabilidades; Racialização; Internamento psiquiátrico; Epistolary practices; Sociability networks; Racialization; Psychiatric admittance; ACCNPQ::Ciências Humanas::História